Collaborative working between speech and language therapists and rehabilitation assistants: An exploratory qualitative study in an interprofessional Community Stroke Team in Northern Ireland/United Kingdom / Zusammenarbeit von Logopäd:innen und Rehabilitationsassistent*innen: Eine explorativ-qualitative Studie in einem interprofessionellen Community Stroke Team in Nordirland/Vereinigtes Königreich - Christofi Christina; Lücking Christiane; Thurmann Anika (International Journal of Health Professions, 2025)
A demographic shift in the UK population has significantly changed the burden of disease. Coupled with staff shortages in allied health professions within the National Health Service, the introduction of assistant roles aimed at freeing up qualified therapists has modernised the professions and challenged traditional practices.